P3-S1.23 Mycoplasma genitalium in South African men with and without symptoms of urethritis: diagnosis and bacterial load. (10th July 2011) - Hoosen, A; le Roux, M C; Adam, A
Abstract : Objectives: To diagnose causes of urethritis in symptomatic men and evaluate the role of Mycoplasma genitalium by calculating bacterial loads in urine specimens from symptomatic and asymptomatic men. Methods: Urine specimens from 94 men with visible urethral discharge, 206 with burning on micturition (BOM) and 75 without any genital symptoms were tested for N gonorrhoeae (NG), C trachomatis (CT), T vaginalis (TV) and M genitalium (MG) using TMA assays. The bacterial load was estimated by quantitative real-time PCR assay in specimens with M genitalium alone. Results: At least one pathogen was detected in 138 (46%); mixed infections in 28 (9.3%). The most common mixed infection was NG + MG (3.7%). There were significant differences for MG (17.3% vs 6.6%), NG (16.7% vs 2.6%), CT (12.3% vs 5.1%), and TV (8.0% vs 1.3%) in symptomatic vs asymptomatic men. There was also a significant difference in presence of MG in the symptomatic men (20.2% in men with discharge vs 4.4% in those with BOM). Patients with urethral discharge (mean 5.3×103 copies/ul) had significantly higher M genitalium concentrations than those with BOM (mean 6.7×102 copies/ul) (p<0.001), and the bacterial concentrations in men with symptoms and/or signs of urethritis were significantly higher than that in asymptomatic men (mean 4.6×101 copies/ul) (p=0.02). Conclusions: Significantly more organisms were detected in patients with urethritis than in those without. There was a strong association between M genitalium bacterial load and men with symptoms of urethritis both BOM and urethral discharge. As the number of organisms increased, the severity of the symptoms increased (greater numbers in urethral discharge), indicating a role for M genitalium in disease severity. This study also demonstrated the usefulness of quantitative PCR in determining an aetiological role and possibility of monitoring efficacy of treatment for this pathogen.